How Advertising Speaks to Consumers: A Case of Youth Language in Local Commercial Discourse - Nor Shahila Mansor (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2021)
Like other developing countries, especially Malaysian urban youths, are continuously creating their “own language” to set themselves apart from the older generation. Referred to as Generation Z or Gen Z (post-millennials), these group of youths use slang that takes the form of code-mixing, abbreviations and ‘nonstandard variety’ of languages. First, this study aimed to reveal the patterns of youth language incorporated into local commercial discourse to attract young-adult consumers. The focus of this study is to determine how youth language is used and at the same time bring forth the different linguistic strategies employed in fashion articles. Secondly, this study investigated the perception of fellow Malaysians, especially young adults, regarding the existence of a youth language, especially code-mixing, in local fashion magazines. This was a qualitative descriptive study, but numbers and percentages were also used to support the findings. The various types of youth language patterns used were gathered based on titles of 60 commercial articles published in 3 famous local fashion magazines, namely Remaja (Youth), Keluarga (Family) and Nona (Woman). The findings showed a high usage of non-standard language and code-mixing in local advertisements. The main reason for using youth language in advertising is to attract and engage the attention of potential target consumers within the Gen Z age group. On the other hand, it was found that most respondents had positive perceptions regarding these kinds of advertisements and consider it as a good marketing skill.